Detection of nitro-organic and peroxide explosives in latent fingermarks by DART- and SALDI-TOF-mass spectrometry - Ma, Jan (2013)
The ability of two mass spectrometric methods, surface-assisted laser desorption/ionization-time of flight-mass spectrometry (SALDI-TOF-MS) and direct analysis in real time (DART-MS), to detect the presence of seven common explosives (six nitro-organic- and one peroxide-type) in spiked latent fingermarks has been examined. It was found that each explosive could be detected with nanogram sensitivity for marks resulting from direct finger contact with a glass probe by DART-MS or onto stainless steel target plates using SALDI-TOF-MS for marks pre-dusted with one type of commercial black magnetic powder. These explosives also could be detected in latent marks lifted from six common surfaces (paper, plastic bag, metal drinks can, wood laminate, adhesive tape and white ceramic tile) whereas no explosive could be detected in equivalent pre-dusted marks on the surface of a commercial lifting tape by the DART-MS method due to high background interference from the tape material. The presence of TNT and Tetryl could be detected in pre-dusted latent fingermarks on a commercial lifting tape for up to 29 days sealed and stored under ambient conditions.